Whole genome sequencing of drug-resistant Mycobacterium tuberculosis isolates in Victoria, Australia - Thinley Dorji; Kristy Horan; Norelle L. Sherry; Ee Laine Tay; Maria Globan; Linda Viberg; Katherine Bond; Justin T. Denholm; Benjamin P. Howden; Patiyan Andersson (International Journal of Infectious Diseases, 2024)
Objectives: Whole genome sequencing (WGS) can identify clusters, transmission patterns, and drug resistance mutations. This is important in low-burden settings such as Australia, as it can assist in efficient contact tracing and surveillance. Methods: We conducted a retrospective cohort study using WGS from 155 genomically defined drug-resistant Mycobacterium tuberculosis (DR-TB) isolates collected between 2018-2021 in Victoria, Australia. Bioinformatic analysis was performed to identify resistance-conferring mutations, lineages, clusters and understand how local sequences compared with international context. Results: Of the 155 sequences, 42% were identified as lineage 2 and 35% as lineage 1; 65.8% (102/155) were isoniazid mono-resistant, 8.4% were multi-drug resistant TB and 5.8% were pre-extensively drug-resistant / extensively drug-resistant TB. The most common mutations were observed in katG and fabG1 genes, especially at Ser315Thr and fabG1 -15 C>T for first-line drugs. Ser450Leu was the most frequent mutation in rpoB gene. Phylogenetic analysis confirmed that Victorian DR-TB were associated with importation events. There was little evidence of local transmission with only five isolate pairs. Conclusion: Isoniazid-resistant TB is the commonest DR-TB in Victoria, and the mutation profile is similar to global circulating DR-TB. Most cases are diagnosed among migrants with limited transmission. This study highlights the value of WGS in identification of clusters and resistance-conferring mutations. This information is crucial in supporting disease mitigation and treatment strategies.